-3t=-6

Simple and best practice solution for -3t=-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3t=-6 equation:


Simplifying
-3t = -6

Solving
-3t = -6

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Divide each side by '-3'.
t = 2

Simplifying
t = 2

See similar equations:

| 3x+21-2y=3 | | 0.1x-0.5z-15=1 | | 10x+10-6x=22 | | 6.8r-2=5.8r-2 | | sin64=p/34 | | 2(1-7m)=-9n+47 | | 5(3x+5)-8x-6=164 | | 20+x=56 | | 12x+18=9+12 | | 2.4x-2.6=17 | | 6(1-7x)=-33-3x | | 5(2c+7)+-3c=7(c+5) | | W=wy | | Y=1/8-3x-2 | | -8(1+8r)=-520 | | v=4/3(3.14)3^3 | | -9+4n+18=7n-24 | | bx-7=3 | | -4t+1=3t+1-7c | | -32=x-12 | | F(n)=8+3(3-1) | | 6x-2+11x-9+5y-8=180 | | vf=244+(12)(7) | | 80+(55d+0.20)=d | | 9=-5g-22 | | 0.8x+0.6y=45 | | 76/ | | 3x+p=x | | 2x+10=76 | | -81=r/-9 | | F=1/3k(d-n) | | 11/2.5= |

Equations solver categories